Molecular structure, spectroscopic assignments and other quantum chemical calculations of anticancer drugs - A review - Ghasemi, A S; Deilam, M; Sharifi-Rad, J; Ashrafi, F; Hoseini-Alfatemi, S M (Cellular and Molecular Biology, 2015)
In many texts, both theoretical and experimental studies on molecular structure and spectroscopic assignments of anticancer medicines have been reported. Molecular geometry parameters have been experimentally obtained by x-ray structure determination method and optimized using computational chemistry method like density functional theory. In this review, we consider calculations based on density function theory at B3LYP/6-31G (d,p) and B3LYP/6-311++G (d,p) levels of theory. Based on optimized geometric parameters of the molecules, molecular structures (length of bonds, bond angles and torsion angles) and vibrational assignments have been obtained. Molecular stability and bond strength have been investigated by applying natural bond orbital (NBO) analysis. Other molecular properties such as mulliken population analysis, thermodynamic properties and polarizabitities of these drugs have been reported. Calculated energies of HOMO and LUMO show that charge transfer occurs in the molecular. Information about the size, shape, charge density distribution and site of molecular chemical reactivity has been obtained by mapping electron density isosurface of electrostatic and compared with experiment data.